PENGARUH ONLINE CUSTOMER RATING DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI E-COMMERCE DENGAN ONLINE CUSTOMER REVIEW SEBAGAI VARIABEL MODERASI (Studi pada Pengguna Shopee di Kota Cilacap) - Tri Wahyuni; Yoestini Yoestini (Diponegoro Journal of Management, 2022)
The rapid development of Information and Communication Technology has an impact on increasing internet users in Indonesia. Where this is used by the community to support daily activities, one of which is to shop online. However, by shopping online there are various risks faced by consumers. This is because consumers do not see and touch the product directly. Therefore, this study was conducted to examine the effect of online customer ratings and celebrity endorsers on purchasing decisions with online customer reviews as moderating variables for Shopee users in Cilacap City. This research was conducted using a questionnaire method using purposive sampling technique to 96 Shopee user respondents in Cilacap City. Then the data analysis methods used include the confirmatory factor analysis test, the full model test, the chisquare difference test moderation test, hypothesis testing, validity testing, reliability testing, and direct effect test, indirect effect, and total effect. Where data testing is carried out using SEM AMOS 22 software. The results showed that online customer rating had a significant effect on purchasing decisions, while celebrity endorsers had no significant effect on purchasing decisions. Then online customer reviews are proven to have a moderating impact on relationship between online customer ratings and purchasing decisions, but online customer reviews have also been shown to not have a moderating impact on celebrity endorsers and purchasing decisions. With the results of this study, it is hoped that it can be a consideration and improvement for Shopee to increase the rating feature to be able to attract more consumers and be selective in choosing celebrity endorsers so that they can influence consumers in the purchasing decision-making process